Comparative analysis of cesarean section using the Robson’s Ten-Group Classification System (RTCGS) in private and public hospitals, Addis Ababa, Ethiopia - Assefa, Endalkachew Mekonnen; Janbo, Adem; Ghiwot, Yirgu (Clinical Journal of Obstetrics and Gynecology, 2021)
Objectives: We analyzed the indications of cesarean section (CS) using Robson Ten-Group. Classification Systems (RTGCS) and comparison between private and public health facilities in Addis Abeba hospitals, Ethiopia, 2017. Methods: Facility-based retrospective cross-sectional study was carried out between January 1 and December 31, 2017, including 2411 mothers who delivered by CS were classified using the RTGCS. Data were entered into SPSS version 20 for cleaning and analyzing. Binary logistic regression and AOR with 95% CI were used to assess the determinants of the CS. Results: The overall CS rate was 41% (34.8% and 66.8% in public & private respectively, p < .0001). The leading contributors for CS rate in the private were Robson groups 5,1,2,3 whereas in the public 5,1,3,2 on descending order. Robson group 1 (nulliparous, cephalic, term, spontaneous labor) and group 3 [Multiparous (excluding previous cesarean section), singleton, cephalic, ≥ 37 weeks’ gestation& spontaneous labor], the CS rate was over two-fold higher in the private than the public sector. Women in Robson groups 1, 2, 5 & 9 are two and more times higher for the absolute contribution of CS in private than public. The top medical indications of CS were non-reassuring fetal status (NRFS, 39.1%) and repeat CS for previous CS scars (39.4%) in public and private respectively. Mothers who delivered by CS in private with history of previous CS scar (AOR 2.9, 95% CI 1.4-6.2), clinical indications of maternal request (AOR 7.7, 95% CI 2.1-27.98) and pregnancy-induced hypertension (AOR 4.2, 95% CI 1.6-10.7), induced labor (AOR 2.5, 95% CI 1.4-4.6) and pre-labored (AOR 2.2, 95% CI 1.6-3.0) were more likely to undergo CS than in public hospital. Conclusion: The prevalence of CS was found to be high, and was significantly higher in private hospitals than in a public hospital. Having CS scar [having previous CS scar, Robson group 5(Previous CS, singleton, cephalic, ≥ 37 weeks’ gestation) and an indication of repeat CS for previous CS scar] is the likely factor that increased the CS rate in private when compared within the public hospital. Recommendation: It is important that efforts to reduce the overall CS rate should focus on reducing the primary CS, encouraging vaginal birth after CS (VBAC). Policies should be directed at the private sector where CS indication seems not to be driven by medical reasons solely.